2017
DOI: 10.1097/pas.0000000000000913
|View full text |Cite
|
Sign up to set email alerts
|

BRAF V600E Mutations Occur in a Subset of Glomus Tumors, and Are Associated With Malignant Histologic Characteristics

Abstract: Glomus tumors are rare mesenchymal neoplasms with a phenotype akin to the modified smooth muscle cells of the glomus body. Most are benign, but rare examples show malignant histologic characteristics and aggressive behavior. We recently encountered a malignant glomus tumor with BRAF V600E mutation. We sought to study a large cohort for this mutation, with particular attention to associated malignant histologic characteristics. Tumors were classified based on WHO criteria as benign, uncertain malignant potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…Tumors > 2 cm in size with atypical mitotic figures, moderate-to-high nuclear grade, and > 5 mitotic figures per 50 high-power fields are considered highly suspicious for malignancy [ 40 ]. A recent study found that BRAF V600E mutations may be associated with a malignant phenotype in glomus tumors [ 41 ]; however, larger cohorts and multicenter studies are required to confirm this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors > 2 cm in size with atypical mitotic figures, moderate-to-high nuclear grade, and > 5 mitotic figures per 50 high-power fields are considered highly suspicious for malignancy [ 40 ]. A recent study found that BRAF V600E mutations may be associated with a malignant phenotype in glomus tumors [ 41 ]; however, larger cohorts and multicenter studies are required to confirm this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Although a rare occurrence, malignant glomus tumors and glomus tumors of uncertain malignant potential have been shown to both be locally aggressive and have the potential to metastasize [ 3 , 9 , 10 ]. Once metastasis occurs, prognosis is poor [ 6 , 8 ]. Wide local excision is the current gold standard treatment option given low potential for glomus tumors with malignant features to metastasize, however surgeons should be privy to this potential outcome prior to surgical intervention [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk of metastasis is low, there have been reports of locally aggressive disease as well as distant metastasis [ 3 ]. Metastatic disease in particular has only been observed in malignant glomus tumors and glomus tumors of uncertain malignant potential [ 8 ], and once metastasized, the disease has a poor prognosis. One study showed 38% (8 of 21 patients) of the patients whose glomus tumors met criteria for malignancy metastasized, and of those patients with metastatic disease, 6 out of the 8 were dead from their disease after 3 years [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most glomus tumors are superficial, less than 2 cm, and surgically curable (52). BRAF V600E appears with a frequency of 6-11% (50,51,53). Its presence in glomus tumors may predict a more aggressive phenotype (53).…”
Section: Glomus Tumormentioning
confidence: 99%
“…BRAF V600E appears with a frequency of 6-11% (50,51,53). Its presence in glomus tumors may predict a more aggressive phenotype (53). Karamzadeh et al reviewed 102 cases, largely originating from the extremities (53).…”
Section: Glomus Tumormentioning
confidence: 99%